Pengaruh Model Pembelajaran Mind Mapping Terhadap Hasil Belajar Siswa Pada Keunikan Daerah Tempat Tinggalku Di Kelas lV SDN Lamsayuen Aceh Besar - Shalihatin, Dian; Israwati, Israwati; Husin, M. (Universitas Syiah Kuala, 2023)
This research is entitled The Effect of Mind Mapping Learning Model on student learning outcomes on the sub-theme of the uniqueness of the area where I live in class IV SDN Lamsayuen Aceh Besar. This study has a problem formulation, namely whether there is a significant effect of the Mind mapping learning model on student learning outcomes in the sub-theme of the uniqueness of the area where I live in class IV SDN Lamsayuen Aceh Besar. The aim of this study is to determine the effect of the mind mapping learning model on student learning outcomes in the sub-theme of the uniqueness of the area where I live in class IV SDN Lamsayuen Aceh Besar. The quantitative approach is the approach used. This study has a type of pre-experimental design and uses one form of one-group pretest and posttest design. The sample in this study were students of class IV SDN Lamsayuen Aceh Besar, totaling 20 students. The test is a data collection technique used. Data analysis technique using t test. The results are based on hypothesis testing of pretest and posttest data with Kolmogorov Smirnov getting the results of the data being normally distributed. Based on the calculation, it can be obtained tcount = 10.47 to compare tcount with ttable, the researcher must find the degrees of freedom, using the formula df=n-1=20-1=19. Then the distribution list t with a significant level = 0.05, then it is obtained that t(1-)(N-1)= t(1.0,05)(20-1)= t(0.95) (19) is 1.73, so it can be concluded that the results obtained by researchers from the data processing t (table) is 1.73. so t(count)t(table) is 10.471.73 then Ho is rejected and H1 is accepted. So the conclusion is that there is a significant difference between the learning outcomes in the pretest and posttest. So from these results the mind mapping learning model can improve learning